STUDY ON PROBABILISTIC SAFETY ASSESSMENT FOR BOX GIRDER OF BRIDGE AND GANTRY CRANE - LUO YouHong; WU Xiao; XIONG Gang; DING ZhengNan (Jixie qiangdu)
Considering the uncertainty of the load,the fracture toughness,the yield strength,the tensile strength,and based on the failure assessment diagram technique（ FAD）,as well as combining with the finite element analysis results of crane structure,the probabilistic safety assessment for box girder of gantry crane is studied. Monte Carlo simulation is used to calculate the failure probability of box girder of gantry crane. The sensitivity of parameters are analyzed to identify the most important parameters that affect the failure probability of box girder of gantry crane. The results show that the yield strength is the most important parameter affecting failure probability,followed by the load and the fracture toughness. The research content provides a reference for the repair,monitoring and safety assessment of box girder of crane.